Perancangan Jaringan Penukar Panas Sederhana Untuk Personal Computer (PC) - Ari Hidayat; Hari Rionaldo; Zulfansyah Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Most energy consumption in the chemical industry is used for temperature change operations. Heat integration method is used to increase energy efficiency on process streams and reducing utility requirement in the production process by installing Heat Exchanger Network (HEN). Design of HEN can be done by software assistance or often called tools for speed up the design time. Therefore software that can be obtained for free and can be developed openly is needed. Program for HEN design is created by Python programming language and applying computational algorithm Maximum Energy Recovery (MER) target calculation using interval-temperature (IT) method and network design using pinch method. The program will be displayed by Graphical User Interface (GUI) using PyQt library on Python.Keyword: heat integration, HEN, software, Python, PyQt